Perancangan Sistem Keuangan Pada PT. Cipta Bina Usaha - Muhammad Ichwan Nur Faiz; Maulana Fajar Fauzi; Feri Iksan Romadhon; Thoyyibah. T (CV. Multi Kreasi Media, 2023)
PT. Cipta Bina Usaha is a company engaged in the field of chemical delivery transportation which is located on Jl. Raya Serpong No.99, Bizhub Warehousing, Block GF No. 8A, Pabuaran Village, Gunung Sindur District, Bogor Regency, West Java. Since 2012, PT. Cipta Bina Usaha has been able to develop delivery areas to several cities. However, this condition makes recording company transaction data more complicated if you only use xls files. The perceived problem is not only the complexity of the recording process, but also maintaining data consistency, especially if transactions occur outside the city. Likewise, company leaders are increasingly finding it difficult to control the development of their company, because there is so much data that cannot be used as valid information. From these problems, the authors offer a solution in the form of a website-based financial reporting application. This application includes recording company financial statements, searching data, and storing data in a MySQL database.